Identification and Phylogenetic Analysis of Bacterial Isolates from Litopenaeus vannamei Shrimp Culture System and Gut Environment Based on 16SrRNA Gene Sequence Data - TUBAGUS HAERU RAHAYU; INDRAWATI GANDJAR; ETTY RIANI; IIN SITI DJUNAIDAH; WELLYZAR SJAMSURIDZAL (Microbiology Indonesia, 2009)
Selected bacterial isolates from a Litopenaeus vannamei shrimp culture system and gut environment were assessed using 16S rRNA gene sequencing method to identify their identity and to construct their phylogenetic relationship. In a preliminary study, a total of 19 isolates were selected as probiotics. These isolates were prepared using freeze and heat-shock method to obtain the DNA template. PCR amplification of 16S ribosomal RNA gene of isolates was carried out using bacterial universal primers 9F and 1510R and was sequenced using an automated DNA sequencer. These gene sequences were compared with other gene sequences in the GenBank database (NCBI) using a BLAST search to find closely related sequences. Alignment of these sequences with sequences available from GenBank database was carried out to construct a phylogenetic tree for these bacteria. Most of the isolates obtained, i.e. 17 out of the 19 isolates, belonged to different species of Bacillus, sharing 95 to 99% 16S ribosomal RNA identity with the respective type-strain, whereas the remaining 2 isolates belonged to Micrococcus sp. and Micrococcus luteus with 97 to 99% 16S rRNA homology, consecutively.